Problematics of the Implementation of Mediation in the Pakam Deli Serdang Religious Court - Roswita Sitompul (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Marriage is something that is considered very sacred in human life and it is as a family for humans to continue their offspring, every human tries to fight to maintain the plume of his household in order to survive, but in terms of the fact that many households have many problems due to many factors. The government in its position as a supervisor and to maintain the presence of community members establish PERMA NO 1 2016 which regulates that every case submitted to the Religious Court must be carried out with mediation. This research is descriptive empirical which data is sourced from primary and secondary data, data collection is done by conducting field research, observations and interviews. The results of the study shows that mediation is failed because: a. the lack of human resources in the Lubuk Pakam Religious Court because there are only 5 Judges, it is not comparable with the current cases and not all Judges can also act as Mediators. b. Unprofessional Attorney who only wants the case to be settled by litigation. c. The parties have unanimous their decision to divorce because they hold too long a longstanding grudge.